PENGARUH PACKAGING PRODUK, MEREK PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO KATULISTIWA KOTA BENGKULU - Dio Saputra; Adi Sismanto (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
The purpose of this study is to determine the influence  of product packaging, and product brands on purchase decisions at the Katulistiwa store in Bengkulu City the population used in this study is 90 respondents. The sampling technique used pourpose sampling based on certain criteria that had been set for a total of 90 respondents. Observation data collection techniques, documentation and questionnaires. The conclusion of the research results is as follows: Product Packaging has a positive effect on consumer Purchase Decisions at the Bengkulu City Katulistiwa Store. Product brands have a positive effect on consumer purchase decisions at the Makkulu City Katulistiwa Store.  Product quality has a positive effect on consumer purchase decisions at the Bengkulu City Equatorial Store. Product packaging, product branding, and product quality affect consumer purchasing decisions. Keywords: Product Packaging, Product Brand, Product Quality, Purchase Decision